Preliminary Study of Skull Polymorphims of Tupaia glis in Peninsular Malaysia by using Morphoj - Azrinaaini, Md Yusoff; Jayaraj Vijaya, Kumaran; Nurul Farah Diyana, Mohd Tahir; Seri Intan, Mokhtar (Penerbit UTM press, 2015)
A Global geographic fragmentation has caused the diversity of animals and plants worldwide, mostly to the population of small mammals. In Malaysia, there a lot of natural barriers that can separate the population of small mammals including common treeshrew,Tupaia glis. In this studey, the polymorphism of ninety (90) Tupaia glis in Peninsular Malaysia is carried out by comparing the skulls of the species from different states by using Morphol analysis. This is carried out to know the landmark of the species and the shape changes.